2018
DOI: 10.1002/stem.2801
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Delivery of Interferonγ-Secreting Mesenchymal Stromal Cells Repolarizes Tumor-Associated Macrophages and Suppresses Neuroblastoma Proliferation In Vivo

Abstract: Neuroblastoma, the most common extracranial solid tumor in childhood, remains a therapeutic challenge. However, one promising patient treatment strategy is the delivery of anti-tumor therapeutic agents via mesenchymal stromal cell (MSC) therapy. MSCs have been safely used to treat genetic bone diseases such as osteogenesis imperfecta, cardiovascular diseases, autoimmune diseases, and cancer. The pro-inflammatory cytokine interferon-gamma (IFNγ) has been shown to decrease tumor proliferation by altering the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 44 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…Today it is well accepted the immunomodulatory role associated to oncolytic virotherapy through several secondary mechanisms derived from the tumor cell infection itself [6]. In our experience, TME changed towards a more inflamed environment, evidenced by the increase of cytokines like CXCL10 and CCL2 [35,36], and the decrease of immunosuppressive molecules (like FoxP3 and Nos2), and molecules that promote tumor growth and invasiveness (like IL10 and TGFβ) [37][38][39]. Therefore, oncolytic virotherapy with Celyvir could have not only a lytic effect in tumor cells, but could also immunomodulate the TME so other therapies can be administered with a higher chance of achieving a clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Today it is well accepted the immunomodulatory role associated to oncolytic virotherapy through several secondary mechanisms derived from the tumor cell infection itself [6]. In our experience, TME changed towards a more inflamed environment, evidenced by the increase of cytokines like CXCL10 and CCL2 [35,36], and the decrease of immunosuppressive molecules (like FoxP3 and Nos2), and molecules that promote tumor growth and invasiveness (like IL10 and TGFβ) [37][38][39]. Therefore, oncolytic virotherapy with Celyvir could have not only a lytic effect in tumor cells, but could also immunomodulate the TME so other therapies can be administered with a higher chance of achieving a clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies have demonstrated anti‐tumor efficacy using genetically‐engineered MSCs to home transgenes to tumor stroma . In these studies, the modified gene either encoded for a secreted protein that had either a direct or indirect effects on tumor cells, or a ‘suicide’ gene that encoded for an enzyme that converted a prodrug into cytotoxic metabolites; an approach known as gene‐directed enzyme‐producing therapy (GDEPT) …”
Section: Introductionmentioning
confidence: 99%
“…We here report on the use of bone marrow derived MSCs engineered with IL7 and IL12 to sustain a CAR T cell attack against colorectal cancer. The concept takes benefit of the unique capacity of MSCs to migrate to and to infiltrate into solid tumors [18] and, upon genetic modification, to produce and deliver transgenic cytokines to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor homing capacity was used to deliver therapeutic products to the tumor site by applying genetically engineered MSCs [11][12][13][14][15][16][17]. In particular, the capacity to actively migrate into the tumor tissue and the ease to engineer the cells by viral vectors makes MSCs attractive for delivering transgenic immune modulators in order to shift the tumor bed from an inhibitory to an immune stimulatory environment [18]. For therapeutic purposes, human MSCs moreover have the advantage that the cells are invisible to allo-recognition which allows using these cells as an allogeneic "off-the-shelf" cell product.…”
Section: Introductionmentioning
confidence: 99%